PENGARUH INDIKATOR FUNDAMENTAL PASAR TERHADAP STRUKTUR MODAL - Helena Novita Kowaup; Irine Herdjiono (Jurnal Akuntansi dan Keuangan (JAK), 2021)
This research aims to analyze the influence of earning per share (EPS), growth opportunity and business risk against capital structure on property companies listed on the Indonesia Stock Exchange. The population in this research was 60 companies that had been ‘go public’ and their shares were listed on the Indonesia Stock Exchange from 2015 to 2018. After the selection was done using a purposive sampling method, a sample of 15 companies was obtained from 2015-2018 so that the total observation of this research is 60. The data used is secondary data and the analytical method used is multiple linear regression analysis. The result of this is partially earning per share is significant negative effect against capital structure, while growth opportunity and business risk is not effect against capital structure. The result of the research simultaneously show earning per share, growth opportunity, and business risk has not effect against the capital structure.